2014
DOI: 10.1016/s2215-0366(14)70301-3
|View full text |Cite
|
Sign up to set email alerts
|

White matter microstructural recovery with abstinence and decline with relapse in alcohol dependence interacts with normal ageing: a controlled longitudinal DTI study

Abstract: Summary Background Alcoholism exacts a toll on brain white matter microstructure, which has the potential of repair with sobriety. Diffusion tensor imaging (DTI) enables in vivo quantification of tissue constituents and localization of tracts potentially affected in alcoholism and its recovery. Extended longitudinal study of alcoholism's trajectory of effect on selective fiber bundles with sustained sobriety or decline with relapse, heretofore, has not been conducted. Methods Tract-based spatial statistics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
101
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 100 publications
(111 citation statements)
references
References 31 publications
10
101
0
Order By: Relevance
“…1) within similar tracts previously reported (Pfefferbaum et al, 2006; Harris et al, 2008; Durkee et al, 2013; Pfefferbaum et al, 2014; Segobin et al., 2015; Sorg et al, 2015). The FA deficits imply disruptions in these fibers due to axonal deletion (de la Monte et al, 2014), demyelination (Pfefferbaum and Sullivan, 2005), and/or microtubule disruptions (Mayfield et al, 2002), which can impair inhibitory control (Baler and Volkow, 2006), working memory, and visuospatial performance in alcohol-dependent individuals (Pfefferbaum et al, 2006).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…1) within similar tracts previously reported (Pfefferbaum et al, 2006; Harris et al, 2008; Durkee et al, 2013; Pfefferbaum et al, 2014; Segobin et al., 2015; Sorg et al, 2015). The FA deficits imply disruptions in these fibers due to axonal deletion (de la Monte et al, 2014), demyelination (Pfefferbaum and Sullivan, 2005), and/or microtubule disruptions (Mayfield et al, 2002), which can impair inhibitory control (Baler and Volkow, 2006), working memory, and visuospatial performance in alcohol-dependent individuals (Pfefferbaum et al, 2006).…”
Section: Discussionsupporting
confidence: 88%
“…Similar recovery of WM microstructure in ALC has been reported using other analysis methods (Gazdzinski et al, 2010; Pfefferbaum et al, 2014). Longitudinal recovery was also reported for WM volumes in ALC over 7.5 months of abstinence (Durazzo et al, 2015) and for the WM microstructure in ALC who abstained for ten years (Pfefferbaum et al, 2014).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…These results were expected for GM [8], but the global nature of associations between alcohol use and WM integrity was surprising; even at an increased significance threshold, approximately 30% of voxels in the WM skeleton showed negative association between AUDIT score and WM integrity. WM damage in adult hazardous alcohol users may be partially reversed with extended abstinence [7577], but the current results underline the importance of increasing efforts for early and effective treatments for AUDs. Further, identification of specific brain regions impacted by alcohol use throughout the lifespan may aid in the development of more efficacious pharmacological treatment options.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Pfefferbaum et al (2014) reported decline in FA across white matter in 56 older individuals over 1–8 years (control sample).…”
mentioning
confidence: 89%